La unidad y triunfo de la Revolución - Pérez Martínez, Lic. Anabel; Rodríguez Hernández, Lic. Elizabeth; Valladares Carvajal, Dr. Francisco de Jesús (Revista Conrado, 2014)
El presente trabajo expone una clase de Historia de Cuba II, República; para estudiantes de 1º año de Estomatología, de la Universidad de Ciencias Médicas de Cienfuegos. El objetivo de la clase es demostrar cómo se logró la unidad de las fuerzas revolucionarias para llevar a cabo la guerra para la plena liberación nacional. Este ejercicio constituye el acto final de evaluación del postgrado de “Pedagogía y Didáctica en la Educación Superior” auspiciado en la UCP “Conrado Benítez García” y posteriormente el acto de evaluación para obtener la categoría de Profesor Instructor. Palabras clave: Clase, estomatología, ejercicio, evaluación. ABSTRACT This pager is about a lesson of History II, the Republic, for students of first year Dentistry at the University of Medical Sciences of Cienfuegos. The objective of this lesson is to demonstrate low was it possible to unite the revolutionary forces to lead them to war and obtain freedom. This exercise is the final activity in the evaluation of the post-grade course entitled “Pedagogy y Didactic en la Education Superior” held at the UCP “Conrado Benítez García” and this exercise will be also taken into account for professors who which to obtain the teaching category of Instructor Professor in future exercises. Keywords: Class, Dentistry, exercise, evaluation.